The Effect of Environmental Disclosure on Company Profitability (Survey on Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2017-2019 Period) - et. al., Shinta Dewi Herawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of environmental disclosure on company profitability. The research method used in this research is explanatory research. This study shows that the relationship between variables is causal, so it is included in the type of causal research. The analytical method used in this research is descriptive statistics, classical assumption tests and hypothesis testing. The results of hypothesis testing show that environmental disclosure has no effect on profitability and the level of environmental disclosure for manufacturing companies from 2017 to 2019 is still low.